Parate Execution of Dependent Rights Categorized as Unlawful Acts - Kusuma Wardhani, Zakiya (International Significance of Notary, 2024)
Abstract : The purpose of this study is to analyze how the implementation of parate execution of dependent rights according to Law Number 4 of 1996 concerning Dependent Rights and why parate execution of dependent rights carried out without permission from the District Court is categorized as unlawful acts.   The method used in this study is using normative juridical research methods, using legal approaches and conceptual approaches. The results of this study show that: first, the implementation of parate execution of collateral auctions bound by dependent rights based on Chapter 1 number 28, Chapter 44 paragraphs (1), (2), (3), (4) and Chapter 45 of the Minister of Finance Regulation Number: 27 / PMK.06 / 2016 dated February 22, 2016 concerning Auction Implementation Guidelines for parate auctions of collateral rights execution based on the Law on Dependent Rights,  There is an "unlawful act" in determining the price limit value of the goods auctioned, if the implementation is not in accordance with applicable laws and regulations. Second, the execution of dependent rights carried out without the approval of the District Court is categorized as an unlawful act,  this refers to the Decision of the Supreme Court of the Republic of Indonesia No. 3201 K / Pdt / 1984 dated January 30, 1986 which affirms that "parate execution carried out without seeking the approval of the District Court even though it is based on Chapter 1178 paragraph (2) of the Civil Code is an unlawful act and auction that done is void". This is also based on SEMA Number 7 of 2012 which states that although the creditor has held the right of dependent, which means the value  of the execution rate, but if the creditor will carry out execution, it must go through  the permission of the Chairman of the District Court, not directly to the Auction Office. If it is done directly to the Auction Office, but the debtor is not willing to vacate the auction object, then the Chief Justice of the District Court is prohibited from executing the emptying of the auction object.Keywords: Parate Executions, Rights of Dependents,